A Novel Trapezoid Concept of Fibula Cutting Guide for Mandible Angle Reconstruction. Issue 5 (July 2021) - Sharma, Shagun; Gaba, Sunil; Nair, Suraj
Abstract : Abstract: Virtual surgical planning (VSP) has revolutionized the planning process in the reconstruction of the mandible with a free fibula flap. The traditional planning and design use a triangular osteotomy guide with a closing wedge movement at the angle. With virtual surgical planning, the authors found an additional lateral mandibular tilt angle and tried to incorporate it in our design of osteotomy guide. The authors have proposed a novel design in a trapezoid shape to accommodate the lateral tilt angle in our osteotomy design. Incorporating the two angles in one angle design improves the aesthesis of the reconstructive procedure and saves operative time.